Blood inflammatory markers, anabolic hormone, vitamin D and L-carnitine status according to frailty status among older adults - Manal Badrasawi,; Suzana Shahar,; Nor Fadilah Rajab,; Devinder Kaur Ajit Singh, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Frailty is associated with functional decline and reduced ability to cope with physiological challenges. The pathophysiological changes in frailty include inflammation, endocrine disturbances, neuromuscular and immune dysfunction. However, comprehensive information on the relationship between biological markers and frailty is scarce. We aimed to determine the relationship between selected biomarkers and frailty among Malaysian older adults. In this cross sectional study, 600 community dwelling older adults were randomly selected from ten different areas in Klang Valley. A total of 382 participants met the inclusion criteria and consented to the study. Out of these, a subsamples of 91 participants were selected for biomarkers analysis. Frailty was defined using Fried’s criteria. Fasting blood glucose, lipid profile, albumin, selected frailty biomarkers including IL-6, TNF- alpha and IGF-1 and vitamin D together with free L-carnitine and acetyl L-carnitine were analysed. The results showed a significantly higher level of serum IL-6 and TNF-α among participants classified as frail as compared to pre-frail and robust (p<0.05). With respect to nutritional biomarkers, binary logistic regression showed that vitamin D deficiency is associated with three times higher risk of frailty (p<0.05). There was no significant relationship between blood L-carnitines and frailty. Further research is required to explore the relationship between L-carnitine and frailty using different parameters involved in L-carnitine homeostasis such as CPTII enzyme and OCTN2 mutation. In conclusion, frailty was associated with increased level of inflammatory markers and vitamin D deficiency. It is empirical to promote healthy lifestyle or disease management to reduce inflammation and increase vitamin D status as one of the frailty prevention action plan among older adults.